Legal Analysis of Human Righta Violayions in Strategic Infrastructure Development in Wadas Village, Purworejo - ANDIKA RAFA HENDRAWAN, ANDIKA RAFA HENDRAWAN; BAGAS DAVA AJI RAMADHAN; Firmansyah Nur Arifin; Sevy Septiana Afina (Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze the forms of human rights violations in the case of Wadas Village and evaluate the state's responsibility based on Law Number 39 of 1999 concerning Human Rights. The focus of the study includes the right to security, land ownership, freedom of expression, and community participation in national strategic development projects. The approach used is qualitative, juridical-sociological, with secondary data collection from legal documents, official reports, journal publications, and media reports. The analysis was conducted using descriptive-thematic and deductive-inductive methods. The findings revealed clear violations, including arrests without warrants, restrictions on citizen participation, and non-compliance with legal procedures by officials. These results emphasize the importance of human rights-based due diligence mechanisms and active community involvement to ensure equitable development.